2016
DOI: 10.1111/and.12709
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the cyproterone acetate-induced testicular hypofunction by a novel nutraceutical lycopene: a genomic approach

Abstract: This study was designed to explore the cyproterone acetate (CPA)-induced andrological hypofunction and its correction by oral administration of lycopene. In this concern, spermatogenic, biochemical, histological and genomic profiles were studied. Cyproterone acetate administration for 1 month helped to develop infertile model rats. A significant recovery was noted in sperm motility, sperm count, sperm viability, hypo-osmotic swelling tail-coiled spermatozoa; activities of testicular ∆ , 3β-hydroxysteroid dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…ANOVA followed by "Multiple-comparison two-tail t test" was performed. Bars with different superscripts (a, b) differ from each other significantly at p < .05 destruction of free radical (Tripathy et al, 2016) after minimising oxidative stress probably because of its remarkable free radical-quenching activity (Mein, Lian, & Wang, 2008) or by activating the antioxidant enzymes after its binding of this nutraceutical to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ANOVA followed by "Multiple-comparison two-tail t test" was performed. Bars with different superscripts (a, b) differ from each other significantly at p < .05 destruction of free radical (Tripathy et al, 2016) after minimising oxidative stress probably because of its remarkable free radical-quenching activity (Mein, Lian, & Wang, 2008) or by activating the antioxidant enzymes after its binding of this nutraceutical to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…It is being noticed that the lycopene has a promising effect on androgenic key enzymes after 30 days treatment in our in vivo study (Tripathy et al, ). But, the direct exposure (in vitro manner) of this nutraceutical on those said enzymes indicated that there was no significant effect of lycopene on above said enzyme activities in CPA+ lycopene‐treated group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations